2005
DOI: 10.1002/jsfa.2111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding complete feed block containing Prosopis cineraria leaves and polyethylene glycol (PEG)‐6000 on nutrient intake, its utilization, rumen fermentation pattern and rumen enzyme profile in kids

Abstract: A study was carried out to determine the effect of replacing the cake portion of concentrate mixture with 5 parts polyethylene glycol (PEG)-6000 in a complete feed block (CFB) containing Prosopis cineraria leaves on the performance, rumen fermentation pattern and rumen enzyme profile of kids under an intensive system of rearing. Eighteen weaners of Sirohi goat of similar body weight (16.0 ± 0.5 kg) and age (90 ± 5 days) were divided into three equal groups. They were housed in individual cages in a side open a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…When PEG was infused into the rumen, populations of those proteolytic bacteria increased significantly (Min et al, 2003). Low NH 3 -N was also reported in sheep (Bhatta et al, 2007) and goats (Bhatta et al, 2002(Bhatta et al, , 2005 consuming tannin-containing Prosopis cineraria leaves (10 g of CT/kg of DM). Ewes grazing the CTcontaining forage L. corniculatus showed lower ruminal NH 3 concentrations than ewes grazing CT-free forage Means within a row without a common superscript letter differ (P < 0.001).…”
Section: Discussionmentioning
confidence: 78%
“…When PEG was infused into the rumen, populations of those proteolytic bacteria increased significantly (Min et al, 2003). Low NH 3 -N was also reported in sheep (Bhatta et al, 2007) and goats (Bhatta et al, 2002(Bhatta et al, , 2005 consuming tannin-containing Prosopis cineraria leaves (10 g of CT/kg of DM). Ewes grazing the CTcontaining forage L. corniculatus showed lower ruminal NH 3 concentrations than ewes grazing CT-free forage Means within a row without a common superscript letter differ (P < 0.001).…”
Section: Discussionmentioning
confidence: 78%
“…Complete FB including roughage have been used by Bhatta et al (2005), who found decreased NH 3 con- Table 5. Chemical composition of solid-associated bacteria (SAB) and liquid-associated bacteria (LAB) isolated from the fermenter contents and from effluents (EB) in single-flow continuous-culture fermenters fed the experimental diets 1 centrations in the rumen than we found in the present experiments (5.4 vs. 7.9 mg/dL).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of browse with high and medium tannin concentration to Eragrostis grass hay decreased acetatic acid production, which is a major product of fibre fermentation but no difference was noted in grass supplemented with browse species having low tannin concentrations. The effects of CT on ruminal VFA concentration and composition vary among studies, depending on dose and source of CT (Bhatta et al 2005). In the study of Khiaosa-Ard et al (2009) using a rumen simulation technique, a decrease in the acetate : propionate ratio was reported when CT extract from A. mearnsii was fed to animals.…”
Section: Volatile Fatty Acid Concentrationmentioning
confidence: 99%